Italian peninsula as a hybridization zone of Ixodes inopinatus and I. ricinus and the prevalence of tick-borne pathogens in I. inopinatus, I. ricinus, and their hybrids - Daněk, Ondřej; Hrbatová, Alena; Volfová, Karolina; Ševčíková, Sylvie; Lesiczka, Paulina; Nováková, Markéta; Ghodrati, Sajjad; Hrazdilova, Kristyna; Veneziano, Vincenzo; Napoli, Ettore; Otranto, Domenico; Montarsi, Fabrizio; et al. (Parasites & vectors, 2024)
BACKGROUND: Ixodes inopinatus was described from Spain on the basis of morphology and partial sequencing of 16S ribosomal DNA. However, several studies suggested that morphological differences between I. inopinatus and Ixodes ricinus are minimal and that 16S rDNA lacks the power to distinguish the two species. Furthermore, nuclear and mitochondrial markers indicated evidence of hybridization between I. inopinatus and I. ricinus. In this study, we tested our hypothesis on tick dispersal from North Africa to Southern Europe and determined the prevalence of selected tick-borne pathogens (TBPs) in I. inopinatus, I. ricinus, and their hybrids. METHODS: Ticks were collected in Italy and Algeria by flagging, identified by sequencing of partial TROSPA and COI genes, and screened for Borrelia burgdorferi s.l., B. miyamotoi, Rickettsia spp., and Anaplasma phagocytophilum by polymerase chain reaction and sequencing of specific markers. RESULTS: Out of the 380 ticks, in Italy, 92 were I. ricinus, 3 were I. inopinatus, and 136 were hybrids of the two species. All 149 ticks from Algeria were I. inopinatus. Overall, 60% of ticks were positive for at least one TBP. Borrelia burgdorferi s.l. was detected in 19.5% of ticks, and it was significantly more prevalent in Ixodes ticks from Algeria than in ticks from Italy. Prevalence of Rickettsia spotted fever group (SFG) was 51.1%, with significantly greater prevalence in ticks from Algeria than in ticks from Italy. Borrelia miyamotoi and A. phagocytophilum were detected in low prevalence (0.9% and 5.2%, respectively) and only in ticks from Italy. CONCLUSIONS: This study indicates that I. inopinatus is a dominant species in Algeria, while I. ricinus and hybrids were common in Italy. The higher prevalence of B. burgdorferi s.l. and Rickettsia SFG in I. inopinatus compared with that in I. ricinus might be due to geographical and ecological differences between these two tick species. The role of I. inopinatus in the epidemiology of TBPs needs further investigation in the Mediterranean Basin.
Keywords: Ixodes ricinus; Italy; RNA, Ribosomal, 16S; Prevalence; Rickettsia SFG; Hybrids; B. miyamotoi; Ixodes; Borrelia burgdorferi s.l.; Algeria; prevalence; mužské pohlaví; Alžírsko; Borrelia burgdorferi; Rickettsia; ženské pohlaví; RNA ribozomální 16S; zvířata; Anaplasma phagocytophilum; Ixodes inopinatus; Hybridization, Genetic; hybridizace genetická; Itálie; nemoci přenášené klíšťaty; klíště; Tick-Borne Diseases; Borrelia; Female; Male; Animals